Long‐term reduction of health care costs and utilization after epilepsy surgery. (23rd December 2015) - Schiltz, Nicholas K.; Kaiboriboon, Kitti; Koroukian, Siran M.; Singer, Mendel E.; Love, Thomas E.
Summary: Objective: To assess long‐term direct medical costs, health care utilization, and mortality following resective surgery in persons with uncontrolled epilepsy. Methods: Retrospective longitudinal cohort study of Medicaid beneficiaries with epilepsy from 2000 to 2008. The study population included 7, 835 persons with uncontrolled focal epilepsy ages 18–64 years, with an average follow‐up time of 5 years. Of these, 135 received surgery during the study period. To account for selection bias, we used risk‐set optimal pairwise matching on a time‐varying propensity score, and inverse probability of treatment weighting. Repeated measures generalized linear models were used to model utilization and cost outcomes. Cox proportional hazard was used to model survival. Results: The mean direct medical cost difference between the surgical group and control group was 6, 806 after risk‐set matching. The incidence rate ratio of inpatient, emergency room, and outpatient utilization was lower among the surgical group in both unadjusted and adjusted analyses. There was no significant difference in mortality after adjustment. Among surgical cases, mean annual costs per subject were on average 6, 484 lower, and all utilization measures were lower after surgery compared to before. Significance: Subjects that underwent epilepsy surgery had lower direct medical care costs and health care utilization. These findings support that epilepsy surgery yields substantial health care cost savings.